Theological Reflections on Selected Adinkra Symbols - Theophilus Effah-Manu; Isaac Boaheng; Nathan Iddrisu Samwini (Journal of Mother-Tongue Biblical Hermeneutics and Theology)
The Adinkra Symbols of the Akan of Ghana are traditional symbols that are ideographical illustrations of sayings, faith, philosophies, thoughts, and values. The Adinkra symbols aid them in socially relating with members of the community and religiously with Nyame (God). The low level of literacy in the continent among others makes the adoption and use of symbols for theological discourse very appropriate. Symbolic theology involves the use of symbols to communicate biblical truths. This study collected data through literature research using secondary sources such as books, articles, and dissertations. The study also administered a structured questionnaire to 110 Christians and 20 Clergy belonging to different denominations. The Theological reflections on the selected symbols showed a convincing correlation between the symbols and the biblical truths. The results from the fieldwork also confirmed the literature: 35% of Christians indicated that the selected symbols were good for Christian use while another 15% said it was good for African Christians. 75% of the clergy also indicated that the symbols were good for Christian use, 47% also said it was very useful and another 47% indicated it was most useful for their line of duty as clergy. The paper seeks to make a case for African Symbolic Theology as a branch of ethno-theology through ethno-hermeneutics. This is on the basis that symbols occupy a huge space in the epistemology and religious space of the people.